The Effect of Classroom Management on Students' Mathematics Learning Motivation - Millah Novita; Rusdi Rusdi (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2021)
This study was motivated by students' low motivation to learn mathematics in a twelfth-grade natural science groupt one of the senior high schools in West Sumatera, Indonesia. One of the alleged contributing factors is the less conducive classroom atmosphere due to the ineffectiveness of the applied classroom management. This study aims to determine the effect of classroom management on students’ mathematics learning motivation. This study was correlational research with the ex post facto nature of research. The study population was the twelfth-grade natural science group at one of the senior high schools in West Sumatera, Indonesia, which consisted of five groups. The data collection technique used was a questionnaire. Samples were taken by non-probability sampling with the purposive sampling technique. The data were analyzed using simple linear regression analysis. The results indicated a correlation between classroom management variables and mathematics learning motivation with a reasonably strong category. Based on the result, it can be concluded that there is a significant effect of classroom management on the students’ mathematics learning motivation.